Boom and bust in capital flows to developing countries: what South Asia can learn from recent financial crises - Peter Nunnenkamp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
Politicians in Asia and some economists contend that developing countries are at the mercy of the rapidly changing winds blowing from international capital markets. We are indeed witnessing another episode of volatility in capital flows, with foreign investors suddenly fleeing emerging markets in Asia. However, speculative attacks are a symptom, rather than the cause of financial turbulences and currency crises in developing countries. In the era of globalization, policy consistency and government credibility have become still more important for sustaining external financing. South Asia would be ill - advised to forgo the benefits of capital inflows in order to avoid the risk of subsequent outflows. Rather, South Asian governments should not repeat the economic policy failures that are underlying the recent crises in Latin America and East Asia.
Keywords: F20; F43; 330; Internationale Kapitalmobilität; Direktinvestition; Entwicklungskonvergenz; Wirtschaftspolitik; Währungspolitik; Glaubwürdigkeit; Institutionalismus; Entwicklungsländer; Südasien